(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
Starting from reflections on the theme of the fold in the Baroque, in the sense given by Gilles Deleuze, as a starting point we go on to trace, within Francesco Borrominiâ€™s work, a figurative continuity between the small and the large, between the detail and the whole work of which it is but a part. Numerous of his original drawings show how the definition of detail takes on a central role in his work, and it may be possible to read in the folds that shape the architectural surfaces of the interior spaces, or of the external faÃ§ades, the same linguistic values that articulate the individual moldings. In Borromini it is evident that the drawing is an instrument of the formation of his language, as it is in his study of antiquity, and has a heuristic function within the design research. The text focuses on an ascalar (here the term ascalar has been coined to signify invariant on any scale) reading of some drawings, in which one can interpret the folds that shape the moldings, as the equivalent articulations of the architectural walls: whether spaces or fragments of imaginary spaces. The perception entrusts to the moving body, and to a new canon of perception, the comprehension of space, but in the detail one must entrust the sense of touch, to follow and perceive, in its entirety, the fold. Â